Formação de docentes para o ensino superior: docência profissional na sociedade contemporânea - Suriani, Rogério Massaro (2020)
This reaserch has as its theme the formation of teachers for higher education and professional teaching in contemporary society. It is located in the Education program: Curriculum in the area of concentration of Educator Formation of the Pontifical Catholic University of São Paulo (PUC-SP). Its approach is the current Brazilian educational scenario in proposing challenges to face the difficulties present in the university educational scenario, through the survey of concepts of pedagogical competences and skills of higher education teachers in order to contribute to the improvement of these teachers and fundamentally basically in Masetto (2018), Tardif (2014), Nóvoa (2019), Perrenoud (2013) and Zabalza (2006). The main hypothesis is that the survey of competences helps in the understanding of the teaching process of higher education and, consequently, the research helps in the reflection of the questions that it proposes to discuss and analyze considering it open to new and possible reflections from the most diverse branches of the humanities